Gestational weight gain, nutritional status and blood pressure in pregnant women - Chiara Alzineth Silva Campos; Maira Barreto Malta; Paulo Augusto Ribeiro Neves; Bárbara Hatzlhoffer Lourenço; Marcia C Castro; Marly Augusto Cardoso
ABSTRACT OBJECTIVE To evaluate whether weekly gestational weight gain is associated with anemia, vitamin A insufficiency, and blood pressure levels in the third trimester of pregnancy. METHODS A prospective study with 457 pregnant women attending primary care in Cruzeiro do Sul, Acre. The weekly gestational weight gain rate measured between the second and third trimesters was classified as insufficient, adequate, and excessive according to the recommendations of the Institute of Medicine 2009. The outcomes at the beginning of the third gestational trimester were: anemia (Hb < 110 g/L), vitamin A insufficiency (serum retinol<1.05 μmol/L) and blood pressure levels (continuous values, in mmHg). Age-adjusted prevalence ratios, schooling, and use of vitamin and mineral supplements were calculated in Poisson regression models with robust variance. RESULTS A total of 18.6% of pregnant women had insufficient weekly weight gain, and 59.1% had excessive weight gain. The frequencies of anemia, vitamin A insufficiency and hypertension (systolic blood pressure ≥ 140 mmHg or diastolic ≥ 90 mmHg) were 17.5%, 13.4%, and 0.6%, respectively. The prevalence ratios for anemia among pregnant women with insufficient and excessive weight gain were 0.41 (95%CI 0.18-0.93) and 1.00 (95%CI 0.63-1.59), respectively, when compared to pregnant women with adequate weight gain. For vitamin A insufficiency, the adjusted prevalence ratio was significantly higher among pregnant women with insufficient weight gain (2.85, 95%CI 1.55-5.24) and no difference for excessive weight gain (1.53, 95%CI 0.84-2.74) when compared to pregnant women with adequate weight gain. Pregnant women with excessive weight gain had higher mean systolic blood pressure (111.10; 95%CI 109.9-112.2) when compared to pregnant women with insufficient weight gain (107.50; 95%CI 105.4-109.6) and adequate (106.20; 95%CI 104.3-108.20). CONCLUSIONS Insufficient weekly gestational weight gain was associated with the risk of vitamin A insufficiency. Excessive weight gain, in turn, was associated with higher blood pressure values at the beginning of the third gestational trimester.